Deep Learning Based Digital Quizzes as A Pathway to Joyful and Meaningful Morphology Learning - Kiki Cahya Muslimah; Anwar Sanusi; Dadang Firdaus (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2025)
Arabic morphology is a crucial yet challenging component of Islamic education due to its structural complexity and conventional teaching methods. This study examines the integration of Genially-based digital quizzes within a deep learning framework to enhance students’ conceptual understanding and engagement in learning Morphology. Using a qualitative intrinsic case study, data were collected through classroom observations, interviews, and digital documentation involving forty female students and one teacher at Persatuan Islam Putri Bangil Islamic Boarding School in Indonesia. Thematic analysis identified five significant learning dimensions: joyfulness, engagement, independent learning, spiritual meaning, and conceptual understanding. The findings show that Genially-based quizzes foster active participation, intrinsic motivation, and reflective thinking, shifting learners from rote memorization toward a meaningful comprehension of morphological patterns. Integrating Qur’anic verses and moral reflection within the quizzes deepened spiritual awareness, resonating with the Islamic educational philosophy of ta’dib, which harmonizes knowledge, ethics, and spirituality. The approach demonstrates that deep learning pedagogy, supported by interactive digital tools, promotes cognitive mastery, affective engagement, and moral growth simultaneously. This model contributes to Sustainable Development Goal 4 (Quality Education) by encouraging inclusive, reflective, and lifelong learning in Islamic education. Despite infrastructural and literacy challenges, the study highlights Genially’s potential as a transformative pedagogical medium that bridges traditional and digital paradigms, advancing Arabic language instruction toward a more holistic, joyful, and spiritually grounded learning experience suitable for the Society 5.0 era.